A New Gonolobus Species (Apocynaceae, Asclepiadoideae) from Sinaloa, Mexico - Leonardo O. Alvarado-Cárdenas; Juan F. Pío-León; Gilberto Morillo; Carla Sofía Islas-Hernández (Taxonomy, 2024)
In this study a new species of Gonolobus, G. villasenorii, is described. It is endemic to Sinaloa, Mexico, distributed in the Sierra Madre Occidental in pine–oak forest. This species is characterized by the presence of lanceolate sepals, margin of the corolla lobes with a whitish-green callus, without being cristate, and anthers with rectangular dorsal appendages. The new species is compared to Gonolobus chloranthus and Gonolobus erianthus. Gonolobus grandiflorus, Gonolobus incerianus, and Gonolobus lozadae are species with which it shares reticulate corollas and flowers more than 2 cm in diameter. A detailed description of the new species includes data on its habitat, ecology, phenology, conservation status, a distribution map, and a section where the new species is compared with similar species and how to recognize it.